Identifikasi Kesulitan-kesulitan yang Dialami Guru-guru Sekolah Dasar di Kabupaten Sorong Selatan - Indri Anugraheni (Jurnal Perkotaan, 2015)
This research is motivated by the fact that many elementary school teachers in the district of Sorong Selatan are still experiencing difficulties in implementing the teaching and learning activities. This study aims to: 1) determine the difficulties experienced by elementary school teachers in South Sorong Regency, 2) to know efforts made by teachers in overcoming the difficulties of learning implementation. The method used in this research is qualitative descriptive naturalistic. The Research steps are: 1) collecting source through a questionnaire, and technical documentation; 2) reducing the data with the aim to simplify and categorize the data; 3) presenting data in the form of a description of the memorial; 4) drawing conclusions as a result of interpretation; 5) preparing research reports. This research was conducted on elementary school teachers who take the Distance Learning Program, which amounted to 123 teachers. Data were collected by distributing questionnaires to teachers from elementary schools in South Sorong Regency. The results showed that teachers of elementary school (Sekolah Dasar) still have many difficulties in implementing the learning process. The difficulties experienced by teachers inteaching include difficulty in: 1) preparing learning activities, 2) developing lesson plans, 2) developing teaching materials, 3) implementing a variety of learning methods, 4) using of media /sources learning, 5) giving reflections to students, 6) comprehensively evaluating learning, and 7) implementing the learning of mathematics.